2015
DOI: 10.1371/journal.pone.0131882
|View full text |Cite
|
Sign up to set email alerts
|

The Quinovic Acid Glycosides Purified Fraction from Uncaria tomentosa Protects against Hemorrhagic Cystitis Induced by Cyclophosphamide in Mice

Abstract: Uncaria tomentosa is widely used in folk medicine for the treatment of numerous diseases, such as urinary tract disease. Hemorrhagic cystitis (HE) is an inflammatory condition of the bladder associated with the use of anticancer drugs such as cyclophosphamide (CYP). Sodium 2-mercaptoethanesulfonate (Mesna) has been used to prevent the occurrence of HE, although this compound is not effective in established lesions. It has been demonstrated that the purinergic system is involved in several pathophysiological ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 33 publications
(60 reference statements)
1
28
0
Order By: Relevance
“…IL-1β and IL-6 are other pro-inflammatory cytokines involved in the process of HC induced by CYP. Elevated bladder levels of IL-1β and IL-6 following CYP were noticed along with increased MPO activity (Arafa, 2009;Dietrich et al, 2015). Acrolein led to induction of the inflammatory cytokines through NF-kB activation, resulting in the production of cytokines like TNF-α and IL-6 as well as ROS (Keles et al, 2014;Wang et al, 2012).…”
Section: Effects Of Cypmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β and IL-6 are other pro-inflammatory cytokines involved in the process of HC induced by CYP. Elevated bladder levels of IL-1β and IL-6 following CYP were noticed along with increased MPO activity (Arafa, 2009;Dietrich et al, 2015). Acrolein led to induction of the inflammatory cytokines through NF-kB activation, resulting in the production of cytokines like TNF-α and IL-6 as well as ROS (Keles et al, 2014;Wang et al, 2012).…”
Section: Effects Of Cypmentioning
confidence: 99%
“…The quinovic acid glycosides purified fraction (QAPF) derived from Uncaria tomentosa (F: Rubiaceae) bark and roots, which have been utilized by the Asháninkas people for various diseases (Keplinger et al, 1998), was reported to have a uroprotective action against CYP-induced HC (Dietrich et al, 2015). A marked reduction in bladder IL-1 and MPO levels was observed with QAPF treatment (Dietrich et al, 2015). Furthermore, the Caesalpinia pyramidalis Tul.…”
Section: Effects Of Cypmentioning
confidence: 99%
“…A 0.4 g von Frey hair monofilament applied 10 times was used to measure the frequency of withdrawal to each forepaw and hind limb, where each withdrawal was measured as 10% of response (75).…”
Section: Neurobehavioral Analysismentioning
confidence: 99%
“…-Garlic [41][42][43][44][45][46] -Astragalus [47][48][49][50][51][52][53] -Uncaria tomentosa [54][55][56][57][58][59][60] Garlic: Allium sativum commonly known as garlic is generally known for its anti-microbial [41] and antihyperlipidaemic [42,43] activity. It is under research for cancer and is meta-analysed for the same [44].…”
Section: Leucocytopeniamentioning
confidence: 99%
“…They are currently researched for anti-inflammatory [58], anti-oxidant [58], denture stomatitis [59], haemorrhagic cystitis [60] and anti-fungal activity [61]. It has also claimed to have a leucocytopenic activity, especially the elevation of monocytes.…”
Section: Leucocytopeniamentioning
confidence: 99%